The spirit of Korean development - Yu, Sang-yŏng (Yonsei University Press, 2015)
The book divides Korea's developmental trajectory into four stages: economic growth, democratization, informtization, and smart power, and analyzes how these four aspects formed a virtuous cycle and advanced.